PENGARUH RETRIBUSI IZIN MENDIRIKAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BULUNGAN - Nur Fitriyani, Nur Fitriyani; Ana Sriekaningsih, Ana Sriekaningsih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
This study are to examine the effect of building permit (IMB) retribution on local income of Bulungan District. To analyzes relationship between dependent and independent variables under this study then exercised simple linear regression method. From the analysis result draw a conclusion that building permit retribution has significant effect on Bulungan’s Local Income. Built on the study result, then can be suggested to the Local Government of Bulungan District to increasing the socialization of the new rule to regulate IMB retribution levy consistent with sufficient time, so it can be more increasing the awareness of the people in meeting the IMB retribution payment obligation. And to improve law enforcement to violation regional rule about IMB retribution by optimizing the role of disciplinary aparatur as well related law enforcer, next to be able to boosting and development of physical means and facilities of Capital Investment and Integrated Permission Office of Bulungan to support and to realize the prime licensing service, and also suggested for the Government of Bulungan District to improving human resource department both quantity and quality in order to be able to managing IMB retribution good and professionally